2009
DOI: 10.1152/ajpendo.90696.2008
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-α and -β and aromatase knockout effects on lower limb muscle mass and contractile function in female mice

Abstract: Estrogen (E2) is reported to regulate skeletal muscle mass and contractile function; whether E2 exerts its effects through estrogen receptor-alpha (ERalpha) or -beta (ERbeta) is unclear. We determined the effect of ERalpha or ERbeta elimination on muscle mass and contractile function in multiple muscles of the lower limb, muscles with different locomotor tasks and proportions of fiber types I and II: soleus (Sol), plantaris (Plan), tibialis anterior (TA), and gastrocnemius (Gast) in mature female mice. To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 53 publications
(43 reference statements)
3
51
0
Order By: Relevance
“…In addition, this positive relationship was unrelated to the testosterone level as the association persisted after its adjustment ( Table 2). The role of estrogen receptor activation in the modulation of muscle mass remains unclear although some animal studies have revealed that estrogen receptor activation was involved in this process (32)(33)(34). Our results also revealed that total E 2 level, though positively related to muscle mass, was negatively related to muscle strength (Tables 2 and 4), in contrary to testosterone that was associated favorably with both muscle quantity and quality.…”
Section: Discussionsupporting
confidence: 45%
“…In addition, this positive relationship was unrelated to the testosterone level as the association persisted after its adjustment ( Table 2). The role of estrogen receptor activation in the modulation of muscle mass remains unclear although some animal studies have revealed that estrogen receptor activation was involved in this process (32)(33)(34). Our results also revealed that total E 2 level, though positively related to muscle mass, was negatively related to muscle strength (Tables 2 and 4), in contrary to testosterone that was associated favorably with both muscle quantity and quality.…”
Section: Discussionsupporting
confidence: 45%
“…It was recently demonstrated that ERa activation is required for normal muscle mass in male mice (31). In addition, there are indications that both ERa and ERb activation modulate muscle mass and/or function in mice (32,33). We also previously showed that E 2 , but not dihydrotestosterone, increased lean mass in orchidectomized, aged male rats (34).…”
Section: Discussionmentioning
confidence: 85%
“…Clinical trials investigating the effects of aromatase inhibition in older men showed no effect of the intervention on body composition or muscle strength (29,30) and, thus, did not support an important role of serum E 2 levels for lean mass in men. Nevertheless, animal studies have indicated that not only AR activation but also ER activation modulates lean mass (31)(32)(33)(34). It was recently demonstrated that ERa activation is required for normal muscle mass in male mice (31).…”
Section: Discussionmentioning
confidence: 99%
“…OVX rats fail to efficiently recover muscle mass after unloading followed by reloading compared with OVX rats treated with estrogens (McClung et al 2006, Sitnick et al 2006, suggesting that estrogens are important for muscle regrowth. By contrast, estrogen receptor alpha (Erα (Esr1))-, but not Erβ (Esr2)-knockout female mice display a significant increase in absolute muscle weight (Brown et al 2009). However, such ERα inactivation results in a decrease in the muscle peak tetanic tension per CSA (Brown et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Because accumulating evidence suggests that estrogens favor muscle regeneration after injury (Brown et al 2009, Velders et al 2012, we next determined the effects of prolonged estrogen insufficiency on satellite cell numbers and functions at 24 weeks after ovariectomy.…”
Section: Muscle Stem Cell Functions Are Impaired In An Estrogen-deficmentioning
confidence: 99%